2023
DOI: 10.4103/ija.ija_294_22
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of clinical effects and recovery characteristics of intraoperative dexmedetomidine infusion with ketamine versus fentanyl as adjuvants in general anaesthesia

Abstract: Background and Aims: Intraoperative dexmedetomidine infusion decreases the concurrent anaesthetic and analgesic requirement. However, because of slow onset and offset, it is often used with other drugs. Opioids have a depressant effect on the cardiorespiratory system while ketamine has the opposite pharmacodynamics. Hence, it was hypothesised that ketamine will have a better intraoperative haemodynamic profile compared to fentanyl. This study compared the clinical effects and recovery characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…16 It has sympathomimetic properties and causes less cardiovascular depression than other induction agents, preserves protective airway reflexes, and has a potent analgesic effect. 15,17,18 While these properties seem beneficial for patients with traumatic brain injury, the use of ketamine in this patient population remains controversial. 19 In the 1970s, multiple studies found that ketamine causes an increase in intracranial pressure, [20][21][22][23] which may increase the risk of adverse outcomes in patients with traumatic brain injury.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%
“…16 It has sympathomimetic properties and causes less cardiovascular depression than other induction agents, preserves protective airway reflexes, and has a potent analgesic effect. 15,17,18 While these properties seem beneficial for patients with traumatic brain injury, the use of ketamine in this patient population remains controversial. 19 In the 1970s, multiple studies found that ketamine causes an increase in intracranial pressure, [20][21][22][23] which may increase the risk of adverse outcomes in patients with traumatic brain injury.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%